1989
DOI: 10.1007/bf00199282
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic induction of lymphokine (IL-2)-activated killer activity by IL-2 and the polysaccharide lentinan, and therapy of spontaneous pulmonary metastases

Abstract: Spleen cells of C57BL/6N mice bearing lung metastases were induced to the cytotoxic state by subcutaneous injection of recombinant human interleukin-2 (IL-2) at a minimum dose of 5 x 10(4) U/mouse three times a day for 3 consecutive days. A single intraperitoneal injection of lentinan alone at concentrations of up to 10 mg/kg body weight did not render spleen cells cytotoxic to P-29 cells, but a combination of subthreshold doses of these agents (5 x 10(4) U/ml IL-2 and 5 mg/kg lentinan) induced significant in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…Similarly, earlier studies have reported that the spiracles of anopheline larvae are plugged due to the entry of fungal spores, causing larval death 39 , 40 . The head of the mosquito larvae is an equally important fungal infection site that supports our observation 41 . Further, we also observed that a few spores were attached to the body surface of the larvae and these spores germinated and penetrated through the larval cuticle, followed by vegetative fungal growth.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Similarly, earlier studies have reported that the spiracles of anopheline larvae are plugged due to the entry of fungal spores, causing larval death 39 , 40 . The head of the mosquito larvae is an equally important fungal infection site that supports our observation 41 . Further, we also observed that a few spores were attached to the body surface of the larvae and these spores germinated and penetrated through the larval cuticle, followed by vegetative fungal growth.…”
Section: Discussionsupporting
confidence: 89%
“…Methanolic extract exhibited larvicidal activity when applied to anopheline larvae. Since many of the compounds have been shown to act synergistically 41 , it is worth testing the cytotoxic and cell growth inhibitory effects of the whole fungal extract rather than its individual components. This principle (synergy) allows for stronger effects when used as a whole products, while quenching or nullifying any unwanted side-effects contributed to the presence of the individual components 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Lentinan is a [31,3-glucan with ~1,6 branches that has been purified completely from Lentinus edodes, an edible mushroom in Japan and found to have characteristic immunomodulatory effects on T cells and to enhance the activities of some macrophages and NK cells in vivo [37]. These agents have been used for the therapy of cancer because of their potential value as biological response modifiers.…”
Section: Discussionmentioning
confidence: 99%
“…Naturally derived polysaccharides including heteroglycans and proteoglycans of certain molecular weight and structure have specific broad-ranged immunomodulatory properties which have been recognized for several decades. Such immunomodulating activity includes activation of macrophages (Adachi et al, 1990), monocytes (Czop and Austen, 1985a), natural killer cells (Peter et al, 1988), lymphocyte activated killer cells (Yamasaki et al, 1989), dendritic cells (Kim, 2007), tumor-infiltrating lymphocytes (Kariya et al, 1991) and other lymphocytes (Kumazawa et al, 1985). The stimulated release of various cytokines including interferons (Kandefer-Szerszen and Kawecki, 1973), interleukins (Sakagami et al, 1988), tumor necrosis factor (Abel and Czop, 1992) and colony stimulating factors (Hashimoto et al, 1990) have also been well documented.…”
Section: Immunomodulatory Property Of Polysaccharides and The β β β βmentioning
confidence: 99%